2007
DOI: 10.1177/1069072705283786
|View full text |Cite
|
Sign up to set email alerts
|

Identity Status, Consistency and Differentiation of Interests, and Career Decision Self-Efficacy

Abstract: Relationships between young adults' identity status, the consistency and differentiation of their career interests, and their career decision self-efficacy were assessed. Among 111 college students, identity status was related to career decision selfefficacy and differentiation of interests, but it was not associated with consistency of interests. In general, more advanced identity status dimensions were associated with higher career decision self-efficacy and more differentiation of interests. The findings hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
1
16

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 27 publications
6
53
1
16
Order By: Relevance
“…Specifically, this research showed that more differentiated interests are related to more stable career aspirations and vocational interests (Bergmann, 1993;Holland, 1968), problem solving abilities (Holland, Gottfredson, & Nafziger, 1975), career maturity for females (Miner, Osborne, & Jaeger, 1997), career choice readiness and vocational identity for adolescents (Hirschi & Läge, 2007), and career certainty (Sackett & Hansen, 1995) as well as a more advanced identity status among college students (Nauta & Kahn, 2007). Others found that poorly differentiated interests are related to less conscientiousness but more openness for female university students (De Fruyt & Mervielde, 1997).…”
Section: Research On Interest Differentiationmentioning
confidence: 99%
“…Specifically, this research showed that more differentiated interests are related to more stable career aspirations and vocational interests (Bergmann, 1993;Holland, 1968), problem solving abilities (Holland, Gottfredson, & Nafziger, 1975), career maturity for females (Miner, Osborne, & Jaeger, 1997), career choice readiness and vocational identity for adolescents (Hirschi & Läge, 2007), and career certainty (Sackett & Hansen, 1995) as well as a more advanced identity status among college students (Nauta & Kahn, 2007). Others found that poorly differentiated interests are related to less conscientiousness but more openness for female university students (De Fruyt & Mervielde, 1997).…”
Section: Research On Interest Differentiationmentioning
confidence: 99%
“…Individuals in the diffuse identity status have many negative characteristics including high neuroticism, low conscientiousness, low levels of agreeableness, low levels of well-being, and fewer internalized values and prosocial behaviours (Clancy, & Dollinger, 1993;Nauta, & Kahn, 2007;Padilla-Walker et al, 2008;Waterman, 2007). In addition, identity diffusion has been associated with general apathy, academic and drug problems, poor interpersonal skills, and those more affected by one's environment.…”
Section: Introductionmentioning
confidence: 99%
“…However, such individuals are also high in neuroticism and low in conscientiousness. They experience low levels of psychological well-being and lack confidence in their ability to make effective career decisions (Clancy, & Dollinger, 1993;Nauta, & Kahn, 2007;Padilla-Walker et al, 2008;Waterman, 2007). Researchers taking a developmental approach to identity argue that individuals tend to spend less time in this status due to the stress associated with its high level of exploration and low commitment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because college is a key time for career decision-making, traditional aged college students have been a focus for career development researchers (e.g., Albaugh & Nauta, 2005;Betz & Borgen, 2009;Brown & Lavish, 2006;Duffy & Klingaman, 2009;Nauta & Kahn, 2007;Scott & Ciani, 2008). Throughout histo~y, one's race and gender (e.g., African American, Latinofa, women) have served as obstacles to the attainment of a college education (Gelber, 2007).…”
Section: Introductionmentioning
confidence: 99%